Analyzing the Concept of Fairness in Polygamy through the Reference of Hadist Nabawi - Abdul Rahman Ramadhan (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
This research aims to analyze and understand the meaning and significance of the concept of